2001
DOI: 10.1016/s0893-133x(00)00229-3
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Hormonal and Behavioral Responses to Hypothyroid and Hyperthyroid States in the Wistar–Kyoto Rat

Abstract: The Wistar-Kyoto (WKY) rat is the normotensive progenitor strain of the spontaneously hypertensive rat (SHR) that Okamoto and Aoki (1963) isolated from a strain of Wistar rats, the Wistar/Hokkaido rat. The WKY rat differs from the SHR not only with respect to resting blood pressure but it also displays smaller stress-induced increases in plasma cathecholamines (McCarty et al. 1987), heart rate, and blood pressure (LeDoux et al. 1982;Rettig et al. 1986;Knardahl and Hendley 1990). In contrast, WKYs show larger e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 56 publications
(60 reference statements)
6
18
2
1
Order By: Relevance
“…In the OFT, WKY rats displayed less line crossing (in terms of the number of times crossed) compared with WIS rats, meaning that WKY rats are hypoactive, in agreement with the findings of previous studies (14,29,32). In addition, in the FST, WKY rats displayed higher immobility -the index of a depressive-like state -compared with WIS rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the OFT, WKY rats displayed less line crossing (in terms of the number of times crossed) compared with WIS rats, meaning that WKY rats are hypoactive, in agreement with the findings of previous studies (14,29,32). In addition, in the FST, WKY rats displayed higher immobility -the index of a depressive-like state -compared with WIS rats.…”
Section: Discussionsupporting
confidence: 92%
“…They display longer immobility in the FST compared with outbred Sprague-Dawley rats and other inbred strains (14,(27)(28)(29)(30); however, chronic antidepressant treatment has been found to alleviate this depression-like behaviour in the FST (31). In addition, WKY rats showed hypoactivity in the openfield test (OFT) compared with WIS rats (14,29,32). This abnormal behaviour in WKY rats corresponds with the findings of a study using human subjects, in which depressed patients exhibited hypoactivity compared with healthy subjects (33).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, some of our results pointed to increased T 3 signaling resulting in enhanced pain perception (Edmondson et al, 1990;Bruno et al, 2005Bruno et al, , 2006. However, in contrast to hy- perthyroid rodents (Redei et al, 2001;Sala-Roca et al, 2002), there was no indication for hyperactivity in Mct8 Ϫ/y mice as shown by unaltered locomotion. We thus speculate that neurons in specific brain regions with direct access to the increased circulating T 3 levels may be exposed to enhanced T 3 signaling, if their T 3 uptake is independent of Mct8.…”
Section: Discussioncontrasting
confidence: 54%
“…In a previous study, 65 severe hypothyroidism was also found to increase immobility in the forced swimming paradigm compared to euthyroid rats, an effect that was prevented by high doses of T4. In other studies, rat strain differences in thyroidal status seem to explain different behavior in the forced swimming test, 66 and TH treatment ameliorates the cognitive and mood impairments caused by alcohol exposure. 67 In our present study, chronic TH treatment restored the depressive-like behavior in parallel with normalization of proliferation in the hippocampus.…”
Section: Discussionmentioning
confidence: 80%